‘Resistance Mixtures’ Reduce Insect Herbivory in Strawberry (Fragaria vesca) Plantations - Koski, Tuuli-Marjaana; de Jong, Sanne; Muola, Anne; Amby, Daniel B.; Andreasson, Erik; Stenberg, Johan A. (Frontiers in Plant Science, 2021)
The transition towards more sustainable plant protection with reduced pesticide use is difficult, because there is no ‘silver bullet’ available among non-chemical tools. Integrating several plant protection approaches may thus be needed for efficient pest management. Recently, increasing the genetic diversity of plantations via cultivar mixing has been proposed as a possible method to reduce pest damage. However, previous studies have not addressed either the relative efficiency of exploiting cultivar mixing and intrinsic plant herbivore resistance or the potential utility of combining these approaches to increase cropping security. Here, using a full factorial experiment with 60 woodland strawberry plots, we tested for the relative and combined effect of cultivar mixing and intrinsic plant resistance on herbivore damage and yield. The experiment comprised two levels of diversity (“high” with ten varieties and “low” with two varieties), and three levels of resistance (“resistant” comprising only varieties intrinsically resistant against strawberry leaf beetle Galerucella tenella; “susceptible” with susceptible varieties only; and “resistance mixtures” with 50:50 mixtures of resistant and susceptible varieties). The experiment was carried out over two growing seasons. Use of resistant varieties either alone or intermixed with susceptible varieties in “resistance mixtures” reduced insect herbivory. Interestingly, resistant varieties not only reduced the mean damage in “resistance mixtures” by themselves being less damaged, but also protected intermixed susceptible varieties via associational resistance. The effect of higher genetic diversity was less evident, reducing herbivory only at the highest level of herbivore damage. In general, herbivory was lowest in plots with high diversity that included at least some resistant varieties, and highest in low diversity plots consisting only of susceptible varieties. Despite this, no significant difference in yield (fruit biomass) was found, indicating that strawberry may be relatively tolerant. Our results demonstrate that combined use of high genetic diversity and resistant varieties can help reduce pest damage and provides a useful tool for sustainable food production. “Resistance mixtures” may be particularly useful for sensitive food crops where susceptible varieties are high-yielding that could not be completely replaced by resistant ones.